Systems and procedures of certification of qualifications in the Federal Republic of Germany - Münch, Joachim [Verfasser]; Henzelmann, Torsten [Verfasser] (My University, 1996)
"This report describes current systems and procedures for certification in Germany. An introduction makes brief reference to the characteristics of the general and vocational training systems. Section 1 contains a preliminary explanation. Section 2 describes the German educational system. Section 3 is a typology of examinations and certificates that can be gained by school attendance, within the dual system, through continuing training, and at universities and establishments of higher education. Section 4 offers an overview of the most important certificates. Five charts that correspond to the five components of the education system--general education schools, vocational training schools, dual system, continuing training, and establishments of higher education--correlate awarding bodies and name of certificate. Section 5 describes the procedures for developing education courses and certificates in the five components of the system. Section 6 discusses individual certificates. Each description includes some or all of these components: short description of the educational course, types and names of certificates, requirements for attaining the certificates, who awards the certificates, what the certificates qualify or entitle the bearer to do, and remarks. Section 7 focuses on certificates as determinants of social and occupational/professional opportunities." (ERIC, BIBB-Doku)
Keywords: G 1.2.3.1 Potenziale; L 7 Prüfungen; S 2.2.4.4 Anerkennung non-formaler Qualifikationen; Bildungsabschluss; Qualifikationsnachweis; Zeugnis; Anerkennung; Zertifizierung; Bundesrepublik Deutschland